The varieties of spiritual experience 21st century research and perspectives - Yaden, David Bryce; Newberg, Andrew 1966- (New York, NY Oxford University Press, 2022)
"In the midst of life's many ordinary moments, some experiences feel extraordinary. They can mark inflection points in one's life, after which one is never quite the same. Most brief experiences capable of making a long-lasting impact involve obvious changes in one's outward circumstances, like a birth, a death, a marriage, or an illness. Yet some life-changing moments seem to come wholly from another source, appearing as mental states or altered states of consciousness either from deep within a person's mind or, perhaps, from a source beyond the self. These experiences have been called by different names over time: spiritual, religious, mystical, peak, or self-transcendent, and people around the world and throughout history have experienced them, up to and including the present day. The sacred texts of every major religion describe these moments, philosophers since the ancient Greeks have pondered them, and according to recent Gallup polls (2003), well over 30% of contemporary Americans have experienced them"--
Hier auch später erschienene, unveränderte Nachdrucke
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Experience (Religion); Spirituality